phân tích thành nhân tử
4a2 - x2 - 2x - 1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^2+2x+1-16=\left(x+1\right)^2-4^2=\left(x+1-4\right).\left(x+1+4\right)=\left(x-3\right).\left(x+5\right)\)
\(x^2+2x+1-16=\left(x^2+2x+1\right)-4^2=\left(x+1\right)^2-4^2=\left(x+1-4\right)\left(x+1+4\right)=\left(x-3\right)\left(x+5\right)\)
`x^2+2x+1-y^2+2y-1`
`=(x^2+2x+1)-(y^2-2y+1)`
`=(x+1)^2-(y-1)^2`
`=(x+1+y-1)(x+1-y+1)`
`=(x+y)(x-y+2)`
Ta có: \(x^2+2x+1-y^2+2y-1\)
\(=\left(x+1\right)^2-\left(y-1\right)^2\)
\(=\left(x+1-y+1\right)\left(x+1+y-1\right)\)
\(=\left(x-y+2\right)\left(x+y\right)\)
\(x^2+2x+1-y^2\)
\(=\left(x+1\right)^2-y^2\)
\(=\left(x+1-y\right)\left(x+1+y\right)\)
\(=\left(x^2-2x+1\right)-\left(y^2-2yz+z^2\right)\)
\(=\left(x-1\right)^2-\left(y-z\right)^2\)
\(=\left(x-1-y+z\right)\left(x-1+y-z\right)\)
\(x^2-2x+1-y^2+2yz-z^2\)
\(=\left(x-1\right)^2-\left(y-z\right)^2\)
\(=\left(x-1-y+z\right)\left(x-1+y-z\right)\)
\(4a^2-x^2-2x-1\)
\(=4a^2-\left(x^2+2x+1\right)\)
\(=4a^2-\left(x+1\right)^2\)
\(=\left(2a+x+1\right)\left(2a-x-1\right)\)
Ta có : 4a2 - x2 - 2x - 1
= 4a2 - ( x2 + 2x + 1 )
= ( 2a )2 - ( x + 1 )2
= ( 2a - x - 1 )( 2a + x + 1 )